A brief review of the geographic ranges and ecological effects of three major invasive cyprinid species in Iran - Ali Reza Radkhah; Soheil Eagderi (Journal of Fisheries)
The present study aimed to investigate the distribution status and ecological effects of the introduction of three major invasive fish species viz. Hemiculter leucisculus, Carassius auratus and Pseudorasbora parva in Iran. This review provides useful information about non-native species for readers. This research can play an important role to protecting aquatic ecosystems in Iran and other parts of the world.